2012
DOI: 10.1515/hsz-2012-0119
|View full text |Cite
|
Sign up to set email alerts
|

Mitophagy: mechanisms, pathophysiological roles, and analysis

Abstract: Mitochondria are essential organelles that regulate cellular energy homeostasis and cell death. The removal of damaged mitochondria through autophagy, a process called mitophagy, is thus critical for maintaining proper cellular functions. Indeed, mitophagy has been recently proposed to play critical roles in terminal differentiation of red blood cells, paternal mitochondrial degradation, neurodegenerative diseases, and ischemia or drug-induced tissue injury. Removal of damaged mitochondria through autophagy re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
714
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 865 publications
(725 citation statements)
references
References 155 publications
(212 reference statements)
7
714
0
4
Order By: Relevance
“…[1][2][3][4] Failure of mitophagy regulation results in abnormal cellular function caused by the accumulation of damaged mitochondria, leading to many pathophysiological states. [5][6][7][8] Accumulating data suggests that mitophagy has an essential role in the regulation of the innate immune response. [9][10][11][12] When mitophagy is impaired, the increase of damaged mitochondria caused by immune stimulators results in the generation of mitochondrial ROS (reactive oxygen species) and release of mitochondrial DNA, which induces hyperactivation of the NLRP3 inflammasome, and in turn leads to over-inflammation, tissue injury and increased mortality in the host.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Failure of mitophagy regulation results in abnormal cellular function caused by the accumulation of damaged mitochondria, leading to many pathophysiological states. [5][6][7][8] Accumulating data suggests that mitophagy has an essential role in the regulation of the innate immune response. [9][10][11][12] When mitophagy is impaired, the increase of damaged mitochondria caused by immune stimulators results in the generation of mitochondrial ROS (reactive oxygen species) and release of mitochondrial DNA, which induces hyperactivation of the NLRP3 inflammasome, and in turn leads to over-inflammation, tissue injury and increased mortality in the host.…”
Section: Introductionmentioning
confidence: 99%
“…The first is preparing damaged mitochondria and the second is activating specific autophagy machinery for the degradation of primed mitochondria. 5 Mitochondrial priming is initiated by PINK1 (PTEN induced putative kinase 1) stabilization and the E3 ubiquitin ligase PARK2/PARKIN (Parkinson disease [autosomal recessive, juvenile] 2, parkin) recruitment to damaged mitochondria. 7,14,15 Activated PARK2 promotes ubiquitination of outer membrane proteins on the mitochondria, which in turn triggers translocation of the ubiquitin-binding receptor SQSTM1 or NBR1 (neighbor of Brca1 gene 1) to mitochondria, thus completing mitochondrial priming.…”
Section: Introductionmentioning
confidence: 99%
“…Macroautophagy was previously considered to be a nonselective process, but recent studies demonstrated that distinct macroautophagy signalling pathways regulate the digestion of specific organelles 12,13 . During erythrocyte maturation, the erythroblasts lose their nuclei to become reticulocytes, which are transformed into erythrocytes (EC) by the elimination of organelles, including the mitochondria.…”
mentioning
confidence: 99%
“…Given the paramount multifacetal roles of mitochondria, selective autophagic removal of dysfunctional mitochondria, mitophagy, is attracting increasing interest. Multiple proteins, including ATG32, Parkin, PTEN-induced putative kinase 1 (PINK1), BNIP3, NIX (also called BNIP3L) and the autophagy adaptor protein p62/SQSTM1, appear to contribute to selectivity during mitophagy [31,32]. Moreover, mitophagy is intimately linked to mitochondrial fusion and fission as discussed in Marin-Garcia and Akhmedov's review [33].…”
mentioning
confidence: 99%